Plumeria Plant Biology, Cultivation Technology And Pest Control Measures (Texas Journal of Agriculture and Biological Sciences, 2024)
Plumeria (lat. Plumeria ) is a highly decorative flowering plant belonging to the family Apocynaceae . These tropical trees or shrubs got their name in honor of the famous botanist and explorer from France Charles Plumier. Heat-loving frangipani can be grown at home, the culture is characterized by rapid growth rates (about 40 centimeters per year). For this reason, the plant requires regular pruning, otherwise, in an uncontrolled state, plumeria will grow up to 2 meters in height and even higher